2020
DOI: 10.1111/ssqu.12858
|View full text |Cite
|
Sign up to set email alerts
|

The Military in Politics and Democracy: Its Impact on Government Spending for Education and Health

Abstract: Objective There is considerable debate over the determinants of government spending, but few studies have considered the impact of the military in politics. This article examines how the military in politics and democracy and the interaction between them might affect the allocation of government spending. Methods I use a variety of econometric specifications, including pooled‐OLS, panel data with random effects and fixed effects estimation, and a panel data set of 129 countries from 1984 and 2013. Further, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Others argue that military spending may exacerbate income inequality if (1) workers in military‐related industries are paid better than those in other sectors, (2) there is an income disparity within the military and ‐related industries between less‐skilled labor (e.g. low‐rank soldiers) and high‐skilled research and development personnel, and (3) military spending crowds out social expenditures, such as education, health, and social transfers (Ali, 2007; Apostolakis, 1992; Biscione & Caruso, 2019; Fan, Wei, & Coyte, 2018; Graham & Mueller, 2019; Kentor, Jorgensen, & Kick, 2012; Shin, 2020). Another group of studies reported a mixed or no significant relationship between military spending and income inequality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Others argue that military spending may exacerbate income inequality if (1) workers in military‐related industries are paid better than those in other sectors, (2) there is an income disparity within the military and ‐related industries between less‐skilled labor (e.g. low‐rank soldiers) and high‐skilled research and development personnel, and (3) military spending crowds out social expenditures, such as education, health, and social transfers (Ali, 2007; Apostolakis, 1992; Biscione & Caruso, 2019; Fan, Wei, & Coyte, 2018; Graham & Mueller, 2019; Kentor, Jorgensen, & Kick, 2012; Shin, 2020). Another group of studies reported a mixed or no significant relationship between military spending and income inequality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A number of other control variables are used for robustness checking. The size of the population aged 65 and above (pop65) represents a demographic cohort that competes for education spending in the form of transfer payments to the elderly population (Shin, 2020;Busemeyer, 2008;Iversen and Stephens, 2008;Avelino, Brown and Hunter, 2005;Brown and Hunter, 1999). Military spending (military) is also expected to compete for education's share of public resources, especially in countries with a large military presence (Shin, 2020;Baqir, 2002).…”
Section: Data and Empirical Methodsmentioning
confidence: 99%
“…The size of the population aged 65 and above (pop65) represents a demographic cohort that competes for education spending in the form of transfer payments to the elderly population (Shin, 2020;Busemeyer, 2008;Iversen and Stephens, 2008;Avelino, Brown and Hunter, 2005;Brown and Hunter, 1999). Military spending (military) is also expected to compete for education's share of public resources, especially in countries with a large military presence (Shin, 2020;Baqir, 2002). The fiscal balance (fiscbal) and gross public debt stock (debt) are both expected to have implications for how much of the public purse is allocated to education (Busemeyer, 2009;Huber, Mustillo and Stephens, 2008;Tilak, 1989Tilak, , 1990.…”
Section: Data and Empirical Methodsmentioning
confidence: 99%
See 2 more Smart Citations